Avaliação das leveduras Torulaspora globosa e Trichosporon asahii no controle da podridão negra em frutos de tomate - Dorta, Caroline (Universidade Federal de São Carlos, 2020)
Post-harvest rot has been responsible for losses by producers, a fact which has limited the commercialization of agricultural products for consumption in natura, fruits and vegetables. The fungus Alternaria alternata is the cause of black rot in post-harvest tomatoes; its control is carried out with fungicides, which contributes to the need for alternatives that present less risk to human health. In that context, yeasts have been studied as biological control agents in fruits. Considering the above, the objective of this research was to determine the potential of the yeasts Trichosporon asahii (3S44) and Torulaspora globosa (5S55) in the control of the fungus A. alternata in tomato fruits. The production of organic compounds volatile (VOCs) was evaluated using closed containers with the inoculated fruit with A. alternata spores, uncovered Petri dishes inoculated with T cells. asahii or T. globosa, and a gauze moistened with sterile distilled water. To the evaluation of yeast survival in the fruit wound, formulations with T. asahii or T.globosa and Tween 80 vehicles, saline, corn starch, colorless gelatin and sodium alginate were inoculated into the tomato wounds, and after 48 hours the portion of the injured region for dilution and plating. The control of the fungus by yeast in the fruit was evaluated by inoculating T. globosa cells in the wounds, and after 3 hours, spores of A. alternata. After 7 days, evaluations of the outer and inner diameter and qualitative assessments. As a result, it was observed in the test of volatile compounds the internal control of the progress of rot in the treatment with T. globosa and decreased spore production in the presence of T. asahii. O corn starch and the yeast Torulaspora globosa showed the best survival results of yeast in the fruit. In the in vivo test of fungus control, the treatment with the yeast T. globosa differed statistically from the control treatment both in relation to external and internal symptom, in addition to decreased production of mycelium. Therefore, the observed results showed that the yeast T. globosa has the potential to control the Alternaria alternata fungus in tomato fruits.
Evaluation of the yeasts Torulaspora globosa and Trichosporon asahii in the control of black rot in tomato fruits
Keywords: Controle fúngico; Formulações de inoculantes; Leveduras rizosféricas; Pós-colheita; CIENCIAS AGRARIAS::AGRONOMIA::FITOSSANIDADE